A Linguistic Odyssey toward Employability: A Tracer Study of the Academic and Professional Development Pathways of AB English Language Graduates - Yongque, Russel Jim J; Tulud, Donnie M; Verona, Mirasol O; Ajero, Orfelina M; Barbosa, Estella B; Dimasingkil, Elangbai B; Colita, Lloyd Anton Von M (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to analyze graduates' demographic profiles, employment status, skills application, and satisfaction dimensions related to leadership, communication, management, and personal development, by situating these outcomes within broader socio-educational expectations about employability and workforce readiness. Methodology: Using a descriptive research design and complete enumeration, data were collected through an online survey administered via Google Forms. The variables included age, gender, civil status, year of graduation, employment status, job position, salary range, and reasons for unemployment. Descriptive statistics were employed to examine patterns in employment conditions, skill utilization, and job satisfaction. Main Findings: Most respondents were 22–35 years old, female, single, and recent graduates (2024). Most graduates were employed, while others pursued further studies, reflecting diverse post-graduation pathways. Employed respondents commonly held contractual or regular positions, with monthly earnings ranging from ₱10,000 to ₱20,000. Communication, critical thinking, and problem-solving skills were identified as essential competencies in the workplace. Salaries and benefits were the most influential factors in job acceptance and retention. While graduates reported overall job satisfaction, they highlighted the need for improved workplace communication, clearer feedback mechanisms, and enhanced opportunities for personal and professional development. Novelty/Originality of this study: This study provides one of the limited tracer-based analyses focusing specifically on AB English Language graduates in the Philippine context. Beyond documenting employment outcomes, it underscores the social significance of tracer studies in evaluating higher education’s responsiveness to labor market realities and graduates’ socio-economic integration. The findings offer evidence-based insights for curriculum enhancement—particularly through project-based learning and qualitative, skills-oriented pedagogies—to strengthen graduate preparedness, career mobility, and long-term professional sustainability.